ANALISIS KINERJA SENSOR PADA ROBOT PENDETEKSI KOTORAN DEBU DAN AIR - Hermawansa Hermawansa; Toibah Umi Kalsum (ILKOM Jurnal Ilmiah, 2019)
Sensors are electronic components that have capabilities that are quite reliable and consist of many types, such as ultrasonic sensors, humidity sensors, and dust sensors. At present almost every electronic equipment is equipped with sensor components, such as the robot designed, equipped with humidity sensors and dust sensors. The purpose of this study is to determine the performance of the humidity sensor and dust sensor in detecting dirt and the sensor sends a signal to the microcontroller, Arduino Mega 2560. From the results of sensor performance research on Arduino-based floor dust and water dust detector robots the proximity sensor response time detects a barrier in a room worth 2 seconds, the dust sensor response time detects dust that is 2 minutes due to improper installation of dust sensors so that slow detecting dust. While the humidity sensor response time in detecting water is 3 seconds. For the performance of the robot on the humidity sensor clean the water on the floor as much as 1 ml for 10 to 17 seconds and to show the robot's performance on the humidity sensor to clean the water as much as 2 ml for 20 to 30 seconds.